A BOOK REVIEW ARTICLE: THE GOLDEN NOTEBOOK - Gerardus Majella Adhyanggono (Soegijapranata Catholic University, 2004)
DORIS LESSING Great Britain: Flamingo HarperCollins Publisher Ltd., 2002, 576pp ISBN: 0-586-08923-3